ANALISIS GEN GSTM1 NULL, GSTT1 NULL, RASIO GSH/GSSG DAN KADAR LOGAM BERAT TERHADAP DERAJAT AUTISM SPEKTRUM DISORDER - Hermawati, Donna; A, Mahayu Dewi; Utari, Agustini; Winarni, Tri Indah; Faradz, Sultana MH (JNH (Journal of Nutrition and Health), 2019)
Background : Autism Spectrum Disorder (ASD) is an behavioral disorder included in multifactorial disease. Several theory said that genetics factor, parental age, immunologic dysfunction, chemical induced, heavy metal intoxication and oxidative stress are related to ASD. A study about genetics and environmental factor is very important. High polymorphism of GSTM1 and GSTT1 genes were reported in autism population. The measurement of heavy metal concentration in hair specimen has been done to know excretion ability of the body. GSTM1 null and GSTT1 null polymorphism in subjects with autism, reflect individual vulnerability for environmental induced, such as heavy metal. Objectives : The objectives of this study was to know the frequency of GSTM1 null and GSTT 1null od ASD patients compare to the wildtype and the heavy metal concentration (Pb and Hg) of ASD patients Methods: Blood samples and hair specimen were collected from thirty eight autism children of Autism School in Semarang, Surakarta and Probolinggo. The Multiplex Polymerase Chain Reaction was used to analyze GSTM1 and GSTT1 gene. The GSH and GSSG concentration were done using ELISA. Heavy metal (Pb) concentration of hair specimen were done using  Atomic Absorption Spectrophotometer. Results : The higher frequency of GSTM1 null & GSTT1 null were obtained in ASD children compared to the wildtype. The average of  Pb concentration reached beyond the maximum standart (3,34 ppm).